History, Capitalism, and Postcolonial Identities: Notes on Archaeologies of the Future - Benavides, O. Hugo (Journal of Contemporary Archaeology, 2019)
In the last four decades there have been critical interventions in archaeology that have engaged the issues of politics, class, and colonialism within the production of the past. A concern in this endeavor has been the role that time has played in the chronological ordering of historical narratives. This article contributes to these debates by assessing narratives of archaeologies of the future, particularly as they have been expressed in Western science-fiction and dystopic texts, focusing in particular on Christopher Priest’s The Affirmation (1981) and Roberto Bolaño’s 2666 (2004, English translation 2009). It assesses how one accounts for such a pernicious system of exploitation as capitalism to have been historicized into a global paradigm, and the complicit role that archaeology plays in this narrative production.